2021
DOI: 10.1016/j.omtm.2021.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy using an ortholog of human fragile X mental retardation protein partially rescues behavioral abnormalities and EEG activity

Abstract: Fragile X syndrome (FXS), a neurodevelopmental disorder with no known cure, is caused by a lack of expression of the fragile X mental retardation protein (FMRP). As a singlegene disorder, FXS is an excellent candidate for viral-vectorbased gene therapy, although that is complicated by the existence of multiple isoforms of FMRP, whose individual cellular functions are unknown. We studied the effects of rat and mouse orthologs of human isoform 17, a major expressed isoform of FMRP. Injection of neonatal Fmr1 kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 55 publications
5
28
0
Order By: Relevance
“…9 ) for gene therapy in Fmr1 KO rats. 2 This FMR1 isoform transcript lacks exon 12 and uses a different acceptor site at exon 17 compared with the longest FMR1 isoform 1 transcript, therefore human FMRP isoform 17 lacks amino acids 376–396 and 580–596 compared with human FMRP isoform 1. Hooper et al.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…9 ) for gene therapy in Fmr1 KO rats. 2 This FMR1 isoform transcript lacks exon 12 and uses a different acceptor site at exon 17 compared with the longest FMR1 isoform 1 transcript, therefore human FMRP isoform 17 lacks amino acids 376–396 and 580–596 compared with human FMRP isoform 1. Hooper et al.…”
Section: Discussionmentioning
confidence: 97%
“…They found that, at age 1.5–2 months, transgene expression partially rescued social dominance and locomotor activity deficits, and abnormal slow-wave activity during the sleep-like state in Fmr1 KO rats. 2 Nevertheless, so far, all reported AAV gene therapy studies used rodent FMRP and the expression was driven by promoters other than the human FMR1 promoter. To apply AAV gene therapy for FXS clinical tests in the future, the therapeutic efficacy of human FMRP expression in appropriate cell types and at physiological levels, preferably driven by the human FMR1 gene promoter should be determined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations